Characterization of the agroecological fair in the municipality of Várzea Alegre, state of Ceará: the case of the São Vicente Farm - Martins, Ana Paula Clementino; de Sousa, Eliane Pinheiro (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2015)
This study aims to characterize the Agroecological Fair of the São Vicente Farm in the municipality of Várzea Alegre, located in the state of Ceará, as well as the effect of the fair on the income obtained by participating families that commercialize their products in this fair. In order to achieve the proposed goals, the methods of table and descriptive analysis and Student’s t test for non-paired data were employed. The Agroecological Fair of the São Vicente Farm is a clear example of the initiatives proposed in the solidary economy, which provides the agents involved with a better quality of life, social inclusion and respect for the environment. Within the agroecological perspective, the fair applies methods and techniques that guarantee good productivity, dismissing the use of agricultural inputs and pesticides that harm nature. The work is conducted by small farmers within the scope of family agriculture, and it brings to these families the opportunity of increasing their income.